Penguatan Nilai-Nilai Pendidikan Karakter dan Moral melalui Program 5S (Senyum Sapa Salam Sopan Santun) di SMK Negeri 1 Trenggalek pada Masa Pandemi Covid-19 - Prezthidya Negtha Zsantana; I Made Suwanda (Kajian Moral dan Kewarganegaraan, 2023)
AbstractTeachers must be able to create a learning environment that can foster character-building attitudes. When implementing online learning, teachers must be creative in utilizing strategies on how to best carry out teacher duties in character building during the pandemic. The most basic character education instilled from an early age, especially in school, is the 5S culture (Greetings, Smiles, Greetings, Politeness, Courtesy). This study aims to describe 1) The formation of character and moral education values through the 5S program (Smile Sapa Salam Courtesy). At SMK Negeri 1 Trenggalek During the Covid-19 Pandemic Period. This research use desciptive qualitative approach. The research informants were the Principal, PPKn teachers, Counseling Guidance teachers and parent. Data collection techniques used participant observation, in-depth interviews and documentation studies. Data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions. The results showed that 1) The implementation of character education through 5S culture (smiles, greetings, greetings, courtesy and manners) during the pandemic was by including character education in the school's vision and mission; include the 5S culture (smile, greet, greet, be polite and courteous) in the spontaneous habituation program; and include 5S activities (smiles, greetings, greetings, courtesy and manners) in the lesson plan. 2) The supporting factor of the 5S program is the existence of teacher resources, the environment and parents of students who support the implementation of the 5S program. The teacher is agile and easy to guide. The inhibiting factor of the 5S program is the presence of students who sometimes behave impolitely, students who are disorganized or undisciplinedKeywords: Character education, 5S program (Greetings, Smiles, Greetings, Politeness, and Courtesy), covid 19